(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article reveals the issues of regional development of cultural tourism, its features as an element of cross-border cooperation. The specifics of the structural organization of cross-border regions formed as a result of the interaction of the border territories of adjacent states are studied. The peculiarities of the organization of tourism activities in cross-border regions are considered, the conditions and opportunities for the development of cultural tourism in them are analyzed. It is established that activities in the field of cross-border tourism should take into account the specifics of the system organization of cross-border regions, as well as the socio cultural features of its main elements.